2019
DOI: 10.20473/jn.v14i3.16933
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Blended Learning on Nursing Students’ Knowledge

Abstract: Introduction: Blended learning is assumed to improve the students’ understanding of learning at nursing school especially in the current industrial revolution 4.0 era.  The combination of classroom and online activities is expected to provide better study outcomes.  This research aimed to compare the knowledge scores of the nursing students in blended learning concerning a research and statistics course at a private faculty of nursing.Methods: The knowledge scores resulted from the student’s score in their mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Additionally, traditional face-to-face learning is associated with several benefits such as shared learning, real-time interaction between faculty–students and student–student and poses less stress compared to BL (Wadesango 2021 ). It is important for the nurse educators to be psychologically prepared to use BL pedagogy to deliver nursing educational content, because BL improves the students’ understanding of learning in nursing schools (Eka, Houghty & Juniarta 2019 ). The same authors confirmed that when BL is used among nursing students, there were positive outcomes, because they paid more interest in learning through face-to-face and online.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, traditional face-to-face learning is associated with several benefits such as shared learning, real-time interaction between faculty–students and student–student and poses less stress compared to BL (Wadesango 2021 ). It is important for the nurse educators to be psychologically prepared to use BL pedagogy to deliver nursing educational content, because BL improves the students’ understanding of learning in nursing schools (Eka, Houghty & Juniarta 2019 ). The same authors confirmed that when BL is used among nursing students, there were positive outcomes, because they paid more interest in learning through face-to-face and online.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research explains the competence of mental health nurses, which is carrying out nursing care, starting from assessment to evaluation (28). Applying a blended learning method was a positive experience for the nursing students in terms of knowledge (15). Students do proper care so that they understand mental health nursing care.…”
Section: Discussionmentioning
confidence: 99%
“…Blended learning is learning that mixes online and offline learning. Blended learning could increase the average knowledge of nursing students as assessed by the results of semester and final exams, which increased from 72.5 to 86.66 (22). Blended learning helps nursing students gain positive experiences to increase their understanding of the learning process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second tool was the motivation scale, which was developed to measure motivation in line with the study questions, making use of the tools employed for prior studies. This tool was developed because the scale was already in its final form, consisting of 28 questions within the three main diminutions of strengthening and ability, sense of value (self-esteem), and knowledge and understanding [ [37] , [38] , [39] ]. As seen in Table 2 below, the table describes measurement Items for motivation, factor loading for the items, and reliability of the whole construct.…”
Section: Methodsmentioning
confidence: 99%